A new Muricea species (Cnidaria, Anthozoa, Octocorallia) from the eastern tropical Pacific - Breedy Shadid, Odalisca (2016)
The genus Muricea is considered abundant and widely distributed along the eastern Pacific. Its occurrence in shallow waters has been recognised; however species from deeper than 30 m have been rarely recorded. During the 2005 R/V Urracá expedition along the north and central Pacific coast of Costa Rica several octocoral specimens were collected by bottom trawling from 30 to 150 m yielding new species and new records. Herein we describe a new species of Muricea from deeper than 30 m. The morphological characters of the species were analysed and illustrated by optic and scanning electron microscopy. Muricea subtilis sp. n. can be distinguished from the other species in the genus by its thin spiny branches, non-imbricate calyces, white colony and sclerites, and the size and composition of sclerites. Comparative character tables are provided for the closest Muricea species-group. This new species increases the number in the genus to 26, and contributes to the knowledge on the diversity and distribution of mesophotic soft corals in the eastern Pacific.